The Adaptation of the Buddhist Death Acceptance Scale for Vietnamese Persons with Cancer - Nguyen H. Long; Sureeporn Thanasilp (Elsevier, 2021)
Purpose: This study reports on selected psychometric properties of the adapted Buddhist Death Acceptance Scale (BDAS) for Vietnamese persons with cancer. Methods: The original 13-item BDAS was developed based on Buddhist perspectives toward death and life and was translated from Thai into Vietnamese. Item content checking with five Vietnamese local experts suggested three items of the original BDAS were irrelevant in Vietnamese culture and hence should be excluded. Psychometric properties of the 10-item BDAS Vietnamese version were tested using a convenience sample of 193 Vietnamese Buddhists with cancer. Results: The internal consistency coefficient of the scale was found to be 0.73. Exploratory factor analysis showed that the 10 items of the BDAS Vietnamese version constituted 2 factors, explaining 51.1% of the variance of death acceptance. The first factor was "acceptance of natural process of death" and the second was "preparing for death." Both factors reflected explicitly Buddhist viewpoints toward death acceptance and were consistent with the original Thai BDAS. However, although similar factors were found, some items in the Vietnamese BDAS did not load to same factors as in the Thai BDAS. Conclusions: The BDAS Vietnamese version provides an initial suitable measurement for death acceptance among Vietnamese Buddhists. Its availability will enable cross-cultural research to investigate death acceptance among Buddhist patients with cancer in Vietnam. However, the differences in item loadings between the Thai and Vietnamese scales suggest that further conceptual and empirical works to refine the measurement are needed.